2006
DOI: 10.1016/j.disc.2005.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Cycle double covers and spanning minors II

Abstract: In this paper we continue our investigations from [R. Häggkvist, K. Markström, Cycle double covers and spanning minors, Technical Report 07, Department of Mathematics, Umeå University, Sweden, 2001, J. Combin. Theory, Ser. B, to appear] regarding spanning subgraphs which imply the existence of cycle double covers. We prove that if a cubic graph G has a spanning subgraph isomorphic to a subdivision of a bridgeless cubic graph on at most 10 vertices then G has a CDC. A notable result is thus that a cubic graph w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Unpublished work by Markström establishes the validity of the CDCC whenever G has a 2‐factor with exactly six components, and Häggkvist and Markström established that the CDCC is true whenever G has a 2‐factor F such that the contraction GF has a circuit containing all odd vertices of GF. Several articles, in particular Goddyn's PhD thesis and an article by Häggkvist and Markström tackle the CDCC via special types of spanning subgraphs called frames; see and the cited literature for details.…”
Section: Introduction and Preliminary Discussionmentioning
confidence: 99%
“…Unpublished work by Markström establishes the validity of the CDCC whenever G has a 2‐factor with exactly six components, and Häggkvist and Markström established that the CDCC is true whenever G has a 2‐factor F such that the contraction GF has a circuit containing all odd vertices of GF. Several articles, in particular Goddyn's PhD thesis and an article by Häggkvist and Markström tackle the CDCC via special types of spanning subgraphs called frames; see and the cited literature for details.…”
Section: Introduction and Preliminary Discussionmentioning
confidence: 99%
“…A cubic graph H is a spanning minor of a cubic graph G if some subdivision of H is a spanning subgraph of G. In [3], Goddyn showed that a cubic graph G has a circuit double cover if it contains the Petersen graph as a spanning minor. Goddyn's result is further improved by Häggkvist and Markström [6] who showed that a cubic graph G has a circuit double cover if it contains a 2connected simple cubic graph with no more than 10 vertices as a spanning minor.…”
Section: Introductionmentioning
confidence: 98%
“…According to their observations [5,6], Häggkvist and Markström proposed the following conjectures. Conjecture 1.3 (Häggkvist and Markström, [5]).…”
Section: Introductionmentioning
confidence: 99%
“…Goddyn's result is further improved by Häggkvist and Markström [23] who showed that a cubic graph G has a circuit double cover if it contains a 2-connected simple cubic graph with no more than 10 vertices as a spanning minor. According to their observations [22,23], Häggkvist and Markström conjectured that every 3-connected cubic graph contains a Kotzig graph as a spanning minor.…”
Section: Introductionmentioning
confidence: 98%
“…Circuit Double Conjecture has been verified for K 5 -minor-free graphs, Petersenminor-free graphs [3] and graphs with specific structures such as Hamiltonian path [47], small oddness ( [27], [24], [26]) and spanning subgraphs ( [20], [22], [23], [51] etc).…”
Section: Introductionmentioning
confidence: 99%